Persistent Infection by a Mycobacterium tuberculosis Strain That Was Theorized To Have Advantageous Properties, as It Was Responsible for a Massive Outbreak - Pérez-Lago, Laura (J Clin Microbiol, 2015)
The strains involved in tuberculosis outbreaks are considered highly virulent and transmissible. We analyzed the case of a patient in Madrid, Spain, who was persistently infected over an 8-year period by the same Beijing Mycobacterium tuberculosis strain. The strain was responsible for a severe outbreak on Gran Canaria Island. The case provides us with a unique opportunity to challenge our assumptions about M. tuberculosis Beijing strains. No clinical/radiological findings consistent with a virulent strain were documented, and the in vitro growth rate of the strain in macrophages was only moderate. No secondary cases stemming from this prolonged active case were detected in the host population. The strain did not acquire resistance mutations, despite constant treatment interruptions, and it remained extremely stable, as demonstrated by the lack of single-nucleotide-polymorphism (SNP)-based differences between the sequential isolates. Our data suggest that the general assumption about M. tuberculosis Beijing strains having advantageous properties (in terms of virulence, transmissibility, and the tendency to acquire mutations and resistance) is not always accurate.